Pediatric Kidney Transplantation in the Developing World: Challenges and Solutions. Issue 9 (19th July 2013) - Rizvi, S. A. H.; Sultan, S.; Zafar, M. N.; Naqvi, S. A. A.; Lanewala, A. A.; Hashmi, S.; Aziz, T.; Hassan, A. S.; Ali, B.; Mohsin, R.; Mubarak, M.; Farasat, S.; et al.
Abstract The prevalence of pediatric RRT and transplantation are low in developing countries, 6–12 and <1 to 5 per million child population (pmcp), respectively. This is due to low GDP/capita of <$10 000, government expenditure on health of <2.6–9% of GDP and paucity of facilities. The reported incidence of pediatric CKD and ESRD is <1.0–8 and 3.4–35 pmcp, respectively. RRT and transplantation are offered mostly in private centers in cities where HD costs $20–100/session and transplants $10 000–20 000. High costs and long distance to centers results in treatment refusal in up to 35% of the cases. In this backdrop 75–85% of children with ESRD are disfranchised from RRT and transplantation. Our center initiated an integrated dialysis–transplant program funded by a community‐government partnership where RRT and transplantation was provided "free of cost" with life long follow‐up and medication. Access to free RRT at doorsteps and transplantation lead to societal acceptance of transplantation as the therapy of choice for ESRD. This enabled us to perform 475 pediatric transplants in 25 years with 1‐ and 5‐year graft survival of 96% and 81%, respectively. Our model shows that pediatric transplantation is possible in developing countries when freely available and accessible to all who need it in the public sector.